A Study to Assess the Factors Contributing for Psychological Well-being among Industrial Workers in Selected Industries of Vadodara - V. , Suresh; Patel, Bhumika; Patel, Bhavisha; Bathula, Jyothi; Bhoi, Rajeshwari; Bariya, Kajal; Bariya, Kiran (International Journal of Psychosocial Rehabilitation, 2020)
Background: Psychological well-being is a vital element of overall well-being. The significance of psychological well-being in working areas has developed in the last 3 decades as physical work has been more diverted into mental work; a person who works mentally feels more psychological trouble at the workplace. Apart from that, the various factors that cause psychological problems in the workplace are bossism, remuneration, and workload. It is observed that around 46% of the working population are having psychological disturbances.Aims and Objectives: The present study aimed to find out the factors affecting psychological well-being among industrial workers in Vadodara.Materials and Method: We conducted a descriptive study in which 60 industrial workers were recruited by using a non-probability purposive sampling technique. A structured questionnaire and interview technique was used and found appropriate to assess the factors affecting psychological well-being. The collected data was tabulated and analyzed by using descriptive and inferential statistics.Results: The overall psychological well-being was observed among the workers; it was found that around 93.33% of workers had moderate positive psychological well-being, about 5% of the sample had low psychological well-being, and 1.6% had high psychological well-being. The present study further revealed that the majority (67.5%) of participants are facing problems with bossism and finding very few opportunities for personal growth.Conclusion: The present study concluded that the worker’s psychological well-being is strongly influenced by the following factors, such as problems with bossism, salary, and lack of opportunity. It is imperative that the employers and policymakers should take appropriate action to promote psychological well-being among workers.